Prevalence of Opiate Use in Ireland 2006: A 3-Source Capture Recapture Study - KELLY, ALAN; Teljeur, Conor; Carvalho, Marlen (Government Publications, Stationary office, Dublin 2, 2010)
This study estimates the prevalence of problem opiate use in Ireland in 2006 using a 3-source capture-recapture method. The three population sources employed to calculate the estimate were the Central (methadone) Treatment List (CTL), the Hospital In-Patient Enquiry Scheme (HIPE) and the Garda list of opiate users.
PUBLISHED
Keywords: Public Health; Opiate use in Ireland